A REVIEW OF THE ETHNOMEDICINAL USES, PHYTOCHEMISTRY AND PHARMACOLOGICAL PROPERTIES OF EKEBERGIA CAPENSIS SPARRM - Maroyi, Alfred (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Ekebergia capensis is an integral part of indigenous pharmacopeia in tropical Africa. The present study critically reviewed the ethnomedicinal uses, phytochemistry, and pharmacological properties of E. capensis. The keywords including E. capensis, its synonyms, English common names, ethnomedicinal uses, and phytochemistry and pharmacological properties of the species were searched using electronic databases such as ISI web of knowledge, ProQuest, science direct, OATD, Scopus, Open-thesis, PubMed, and Google Scholar. Pre-electronic literature of conference papers, scientific articles, books, book chapters, dissertations, and theses was carried out at the University Library. Literature studies revealed that E. capensis is mainly used as herbal medicine against fever and malaria, gastrointestinal problems, pain, parasitic worms, reproductive problems in women, respiratory problems, and skin diseases. Phytochemical compounds identified from the species include alkaloids, anthraquinones, coumarins, flavonoids, glycoflavonoids, glycosides, iridoids, limonoids, polyphenols, phytosteroids, pregnane, saponins, tannins, and withanolides. Pharmacological studies revealed that E. capensis extracts and compounds have acetylcholinesterase-inhibitory, analgesic and anti-inflammatory, anthelmintic, antibacterial, antifungal, antigonococcal, antimycobacterial, antimycoplasmal, antihypertensive, antioxidant, antimalarial and antiplasmodial, antischistosomal, antitrypanosomal, and antiviral and cytotoxicity activities. Although pharmacological evaluations carried out so far have confirmed the potency of E. capensis crude extracts and compounds, detailed studies are required aimed at establishing the efficacy, clinical relevance, safety, and mechanisms of action of the plant extracts and compounds.